Optimization of Small-Scale Coffee Roasting Machine with Servo Temperature and Angle Control for Consistent Roasting Results - Purnata, Hendi; Supriyono, Supriyono; Kurniabayu, Marshal; Abshor, Raafi (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2025)
The coffee roasting process is essential for creating distinctive aromas and Flavors. Manual roasting often results in uncontrolled temperatures, resulting in uneven and burnt coffee beans. Therefore, an automatic roasting machine was developed to control stable temperatures at setpoints of 180°C (light roast), 220°C (medium roast), and 250°C (dark roast), with a monitoring system to ensure optimal results. Servo angle settings are used to optimize temperature stabilization, while a DC fan serves to remove excess heat from the machine. The system uses an Arduino Uno and ESP32, with a Thermocouple Type K temperature sensor and an I2C LCD display for real-time monitoring. Integration with IoT Blynk allows remote monitoring and control through a mobile application. Research shows that a servo angle of 140° provides the optimal temperature increase, while an angle of 100° is effective for lowering the temperature when it exceeds the setpoint. These angles are used in the system to keep the temperature controlled according to the specified target.